2005
DOI: 10.1213/01.ane.0000158611.15820.3d
|View full text |Cite
|
Sign up to set email alerts
|

Tutorial: Context-Sensitive Decrement Times for Inhaled Anesthetics

Abstract: Context-sensitive decrement times for inhaled anesthetics connect two values: a) the duration of anesthesia (nominally at a constant alveolar concentration)-the "context" and b) the time to decrease the alveolar or vital tissue (e.g., brain, heart, kidney, and liver, collectively called the vessel-rich group of tissues) concentration by some fractional "decrement" of the starting concentration. Increasing duration of anesthesia increases the time to a given decrement in a nonlinear manner that may considerably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 38 publications
3
49
0
1
Order By: Relevance
“…We recently simulated the time course of recovery for sevoflurane, desflurane, and isoflurane, assuming an individual of normal weight [10]. Our findings confirm those of Bailey and explain the results of Arain et al We found that if the concentration in the vessel-rich group needs to decrease by 80% or less at the end of anesthesia, then the differences in time course between sevoflurane and desflurane are minimal.…”
Section: The Complexity Of Recovery From Anesthesiasupporting
confidence: 82%
“…We recently simulated the time course of recovery for sevoflurane, desflurane, and isoflurane, assuming an individual of normal weight [10]. Our findings confirm those of Bailey and explain the results of Arain et al We found that if the concentration in the vessel-rich group needs to decrease by 80% or less at the end of anesthesia, then the differences in time course between sevoflurane and desflurane are minimal.…”
Section: The Complexity Of Recovery From Anesthesiasupporting
confidence: 82%
“…From the context-sensitive decrement times for inhalation anesthetics, the percentage reduction in extubation time with desflurane (vertical axis) is likely larger for patients with long extubation times at baseline (horizontal axis). 70,71 The linear weighted rank regression slope shown equals 1.3% per minute (P ϭ 0.029) (SYSTAT 12, Systat Software, San Jose, CA). The corresponding value without weighting equals 1.1% per minute (P ϭ 0.014).…”
Section: Disclosurementioning
confidence: 99%
“…[8] The total body uptake and elimination period of isoflurane are supposed to be proportional to the administered concentrations and duration of general anesthesia according to computer simulation. [21] In this study, the awakening time was 18.5 minutes after discontinuing 1.29 MAC isoflurane, which was longer than 15.5 minutes in pediatric neurosurgical patients receiving maintained 0.9 to 1.0 MAC isoflurane. [5] Furthermore, the actual arterial blood concentration of isoflurane was 1.18% at the end of mean 330-minute cardiac surgery in our previous 20-minute pharmacokinetic study, [10] which was higher than 0.84% in this mean 108-minute study.…”
Section: Discussionmentioning
confidence: 98%